Evaluación del rendimiento en la determinación de aceite esencial y pectina de tres cítricos limón “chino”, mandarina “criolla” y toronja “blanca” en el cantón Ventanas año 2014. - Coello Salazar, Sully Caroly (2014)
This research was conducted at the State Technical University of Quevedo, located Av Quito km. 11/2 pathway Tsachilas of Santo Domingo, Province of Los Ríos. The research was conducted between September and November 2013. " Performance evaluation in the determination of essential oil and lemon citrus pectin three " Chinese " Mandarin " Creole " grapefruit and " White "in Canton windows 2014 " The objectives were ; . (1) Set - physical parameters chemical and nutritional fruit lemon "Chinese‖ mandarin " Creole" grapefruit and "White‖ in two stages of maturity. (2) Determining quality parameters essential oil of lemon zest, ―Chinese",‖ Creole" mandarin "white " grapefruit based on their performance, chromatographic characteristics and state of maturation. (3) Obtain the residual pectin lemon zest "Chinese‖ Mandarin ―Creole" grapefruit and "White‖, reducing the time of acid hydrolysis extraction. Treatments consist of three citrus varieties in two states of maturity, according to the design of randomized complete block in the physical -chemical 2 reps and pectin in 3 replicates. The variables measured were , equatorial diameter, polar diameter , unit weight , volume , density, content of juice, juice yield, seed weight , seed number , pH, brix , Titratable acidity , maturity index , dry matter, moisture , ash, protein , ether extract, nitrogen-free extract , vitamin C , total sugars , reducing sugars , calcium , phosphorus , magnesium, potassium , sodium, for comparison of means test was used Tukey at 5% probability. As for the results, the highest juice content is presented in the T6 corresponding to the Grapefruit "White " state of mature maturity with 109.52 ml , chemical parameters was determined that the best state of maturity for obtaining juice is the green state , which are within the parameters of Endocrinology . Eventually the essential oil was evaluated by gas chromatography. As pectin higher values obtained were the same on the skin of the fruit when ripe.